Asynchronous Transaction Commitment in Federated Database Systems - HWANG, San-Yih (Institutional Knowledge at Singapore Management University, 1993)
We propose a new (and restricted) model for global transactions which allows asynchronous commitment of subtransactions. Our model requires each global transaction to have a fixed structure with update to the data in at most one database. Based on this transaction model, we present two concurrency control algorithms, namely Asynchronous Site Graph and Asynchronous VirtGlobalSG, which employ asynchronous commitment and achieve global serializability. Compared to other proposed algorithms, our algorithms employ asynchronous commitment so as to increase transaction performance. Furthermore, our algorithms do not put restrictions on transaction data access or local histories.